2022
DOI: 10.5194/gmd-2021-437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty and sensitivity analysis for probabilistic weather and climate risk modelling: an implementation in CLIMADA v.3.1.0

Abstract: Abstract. Modelling the risk of natural hazards for society, ecosystems, and the economy is subject to strong uncertainties, even more so in the context of a changing climate, evolving societies, growing economies, and declining ecosystems. Here we present a new feature of the climate risk modelling platform CLIMADA which allows to carry out global uncertainty and sensitivity analysis. CLIMADA underpins the Economics of Climate Adaptation (ECA) methodology which provides decision makers with a fact-base to und… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Quantitative risk assessment frameworks such as CLIMADA (Aznar-Siguan and Bresch, 2019) provide a useful tool for carrying out global U&SA, as they can be repeatedly applied with minimal computational expense. Kropf et al (2022) present an extension of the CLIMADA platform that seamlessly integrates the SALib -Sensitivity Analysis Library in Python package (Herman and Usher, 2017) into the overall CLIMADA modelling framework, via the UNcertainty and SEnsitity QUAntification (unsequa) module. Following similar steps as a generic U&SA (Pianosi et al, 2016), their approach requires the specification of a probability distribution for each of the uncertain input factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative risk assessment frameworks such as CLIMADA (Aznar-Siguan and Bresch, 2019) provide a useful tool for carrying out global U&SA, as they can be repeatedly applied with minimal computational expense. Kropf et al (2022) present an extension of the CLIMADA platform that seamlessly integrates the SALib -Sensitivity Analysis Library in Python package (Herman and Usher, 2017) into the overall CLIMADA modelling framework, via the UNcertainty and SEnsitity QUAntification (unsequa) module. Following similar steps as a generic U&SA (Pianosi et al, 2016), their approach requires the specification of a probability distribution for each of the uncertain input factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…when the underlying statistical model for the input factor has been derived within the study allowing for a quantification of uncertainty. However, as noted by Kropf et al (2022), when this information is not available it is often not evident how to perturb the inputs, and in particular it is difficult to define physically consistent statistical perturbations of geospatial data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the level of risk imposed by a certain physical disturbance on a natural or socioeconomic system, the three components of risk defined in the ICs framework (i.e., hazard, exposure and vulnerability; Reisinger et al, 2020), are combined in climate risk models (Kropf et al, 2022). In these types of models, indicators for the hazard (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the different nature of the input data complicates the quantification of the final risk. Particularly, obtaining robust verification data for the exposure and vulnerability components can be quite challenging (Kropf et al, 2022), since these elements are sometimes identified from subjective methods (Zommers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%